2013
DOI: 10.1073/pnas.1315862110
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 activation in response to IL-6 is prolonged by the binding of IL-6 receptor to EGF receptor

Abstract: The activation of STAT3 by tyrosine phosphorylation, essential for normal development and for a normal inflammatory response to invading pathogens, is kept in check by negative regulators. Abnormal constitutive activation of STAT3, which contributes to the pathology of cancer and to chronic inflammatory diseases such as rheumatoid arthritis, occurs when negative regulation is not fully effective. SOCS3, the major negative regulator of STAT3, is induced by tyrosine-phosphorylated STAT3 and terminates STAT3 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
224
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(238 citation statements)
references
References 37 publications
10
224
1
3
Order By: Relevance
“…The biphasic pattern of Y705 phosphorylation of STAT3 in Fig. 4C is in accord with our previous observations (17). The IL-6-induced expression of three genes whose expression is inhibited by the K49R mutation, SERPINA1, SOCS3, and GADD45G, also was inhibited when EZH2 was knocked down (compare Fig.…”
Section: Stat3supporting
confidence: 91%
“…The biphasic pattern of Y705 phosphorylation of STAT3 in Fig. 4C is in accord with our previous observations (17). The IL-6-induced expression of three genes whose expression is inhibited by the K49R mutation, SERPINA1, SOCS3, and GADD45G, also was inhibited when EZH2 was knocked down (compare Fig.…”
Section: Stat3supporting
confidence: 91%
“…These two proteins can also affect signaling pathways indirectly through regulation of downstream cytokines. IL-6 and TNF-α play particularly important roles, because they can form feedback loops with STAT3 and NF-κB, respectively (29,30). We found that IL-6 treatment not only increased the phosphorylation of STAT3 but also increased the expression of SMYD2 ( Figure 6E), and that treatment with TNF-α also increased the phosphorylation of p65 and the expression of SMYD2 ( Figure 6F).…”
Section: Silencing Smyd2 Decreased Phosphorylation and Activation Of mentioning
confidence: 76%
“…In contrast, the activation of STAT1 by IFNγ stimulation resulted in potentiation of miR‐7 transcriptional activity; here, we suggest that this was through ISRE, ISGF3G, and upstream STAT1 binding sites. Levels of STAT3 bound to the miR‐7 promoter probe, observed in E2‐treated young fibroblasts, may be causative of increased EGFR expression and activity, as recent research has identified an increase in STAT3 signaling in the presence of EGFR/IL6R association and co‐activation (Wang et al ., 2013). STAT1 forms complexes with STAT2 and IRF9 to activate ISGF3G/ISRE (Darnell et al ., 1994); however, STAT3 suppressed STAT1‐dependent gene activation and inhibited STAT1 heterodimer formation (Ho & Ivashkiv, 2006).…”
Section: Discussionmentioning
confidence: 99%